1997
DOI: 10.1007/bf02974002
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid, an antioxidant principle from the aerial parts ofArtemisia iwayomogi that acts on 1,1-diphenyl-2-picrylhydrazyl radical

Abstract: The antioxidant activity ofArtemisia iwayomogi was determined by measuring the radical scavenging effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical The methanol extract ofA. iwayomogi showed strong antioxidant activity, and thus fractionated with several solvents. The antioxidant activity potential of the individual fraction was in the order of ethyl acetate>n-butanol>water>chloroform>n-hexane fraction. The ethyl acetate andn-butanol soluble fractions exhibiting strong antioxidant activity were further pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…In contrast, the H 2 O-soluble fraction exhibited weak scavenging activity, indicating that the active principles may be concentrated in the non-polar layer. Therefore, we next tried isolation of the active compounds from the EtOAc-, and the n-BuOH-fractions on the basis of previous paper (Kim et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the H 2 O-soluble fraction exhibited weak scavenging activity, indicating that the active principles may be concentrated in the non-polar layer. Therefore, we next tried isolation of the active compounds from the EtOAc-, and the n-BuOH-fractions on the basis of previous paper (Kim et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The powdered aerial parts (1.25 kg) of A. iwayomogi were extracted with MeOH and concentrated to give a dark residue (850 g), which were partitioned with CH 2 Cl 2 (30 g), EtOAc (70 g), n-BuOH (240 g), and H 2 O (330 g) successively. The EtOAc (10 g) and n-BuOH (10 g) fractions exhibiting high ONOO − scavenging activities were further isolated according to a procedure described in a previous paper (Kim et al, 1997) to obtain: (1) apigenin 7-methylether (genkwanin, 50 mg); (2) scopoletin (200 mg); (3) jaceosidin (80 mg); (4) apigenin 7,4′-di-O-methylether (40 mg) from the EtOAc fraction; (5) chlorogenic acid (400 mg); (6) 2,4dihydroxy 6-methoxy acetophenone 4-O-β-D-glucoside (500 mg); (7) quebrachitol (2 g); and (8) scopolin (600 mg) from the n-BuOH fraction.…”
Section: Introductionmentioning
confidence: 99%
“…viridis Besser, Compositae), locally known as Haninjin or Dowijigi, is a perennial herb easily found in Korea (17). The aerial part of A. iwayomogi has traditionally been used for antitumour, immunomodulating, antimutagenic, antioxidant, antibacterial, antifungal, and liver protective effect and choleretic purposes in Korea (2,16,19,30).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 – 20 isolated from A. iwayomogi were identified as scopoletin ( 1 ) [11, 24], scopolin ( 2 ) [11, 24], genkwanin ( 3 ) [11], hispidulin ( 4 ) [25], jaceosidin ( 5 ) [11, 26], 6-methoxytricin ( 6 ) [26], arteanoflavone ( 7 ) [27], patuletin-3- O -glucoside ( 8 ) [28], isoquercetin ( 9 ) [24, 29], quercetin-3-gentiobioside ( 10 ) [29], rutin ( 11 ) [30], 3- O -caffeoylquinic acid ( 12 ) [24], 1,3-di- O -caffeoylquinic acid ( 13 ) [31], 3,4-di- O -caffeoylquinic acid ( 14 ) [32], 3,5-di- O -caffeoylquinic acid ( 15 ) [24, 32], 3,5-di- O -caffeoylquinic acid methyl ester ( 16 ) [32], iwayoside A ( 17 ) [33], suavioside A ( 18 ) [34], sugeroside ( 19 ) [34], and 2,4-dihydroxy-6-methoxyacetophenone 4- O - β - d -glucopyranoside ( 20 ) [11] by comparison with the spectroscopic data ( 1 H-NMR, 13 C-NMR, and MS) from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…A. iwayomogi has long been used in Korea in vegetables and foods such as tea, rice cake, and soup and also used for the treatment of various diseases including hepatitis, inflammation, and immune-related diseases as a protection for the liver, and a diuretic [8–10]. Previous studies have reported the isolation of scopoletin, esculetin 6-methylether, scopolin, β -sitosterol, chlorogenic acid, quebrachitol, essential oils, fatty acids, sesquiterpene lactones, and flavonoids in A. iwayomogi [1114]. Among them, scopolin modulated the expression of obesity-associated genes and was shown to have pharmacological effects on obesity, fatty liver, and diabetes [15].…”
Section: Introductionmentioning
confidence: 99%